Comparison of knowledge, awareness, and behaviors toward oral cancer among dental students and dentists: an online cross-sectional questionnaire in Türkiye - Serap Keskin Tunç; Mehmet Emin Toprak; Esra Yüce; Nihat Efe; Celalettin Topbaş (BMC, 2024)
Abstract Objective This cross-sectional online questionnaire-based study evaluated the knowledge, awareness, and behaviors of dentists and senior dental students regarding oral cancer (OC). Materials and methods This study included 168 dentists and senior dental students who had completed all theoretical educations and clinical practices. An online survey was administered to all participants to assess their awareness of the risk factors for OC, clinical knowledge, and behaviors. The participants' demographic characteristics and knowledge of OC were analyzed. Results Of the participants, 48.8% were female and 51.2% were male. Their mean age was 27.04 ± 5.56 years (range: 21-51). In addition, 59.5% were dentists, and 40.5% were senior dental students. The dentists' mean time since graduation was 6.38 ± 5.64 years (range: 1-27). Routine oral mucosa examination for OC was significantly more frequent among the dentists than the senior dental students (p < 0.05). Among all participants, 33% of dentists and 51.5% of senior dental students had poor knowledge of OC-related or possibly predisposing factors. Routine evaluation of OC-related and predisposing risk factors, including human papillomavirus infection, smoking, alcohol use, trauma-related non-healing oral lesions caused by long-term incompatible prostheses, and poor oral hygiene, was significantly more frequent among the dentists than the senior dental students (p < 0.05). Conclusion Educating dental students about a more comprehensive oral examination and early diagnosis of OC would help overcome the current lack of adequate knowledge and attitudes in OC prevention and early detection. A core curriculum compatible with the global standards on OC should be provided to dental students.